Identifikasi Pencemaran Air Sungai Batang Tebo di Kabupaten Bungo Berdasarkan Parameter Fisis dan Kimia - Raudahtul Janah; Afdal Afdal (Jurnal Fisika Unand, 2024)
This research aims to determine the level of water pollution in the Batang Tebo River in Bungo Regency based on physical and chemical properties. The chemical parameters calculated are pH and concentration of heavy metals Hg, Pb, and Cu. The physical parameters calculated are TDS, TSS, temperature, and turbidity. All parameters except TSS, turbidity, and heavy metal concentrations were measured in the field. The level of river water pollution is analyzed using the Pollution Index (IP). The research results show that the Batang Tebo River water in Bungo Regency is classified as lightly polluted, with an IP value of 4.12. Physical parameters that have exceeded quality standards are a TSS value of 343 mg/L and a turbidity value of 69.60 NTU. In contrast, those that have not exceeded quality standards are temperature values of 29ºC, TDS values of 23 ppm, and electrical conductivity values of 47 µS/cm. Chemical parameters that have exceeded the quality standards, namely the concentration of the heavy metal mercury of 0.0023 mg/L, while those that have not exceeded the quality standards, namely the pH value of 6.58, the concentration of the heavy metal lead is ˂0.005 mg/L, and the concentration of the heavy metal copper is ˂0.018 mg/L.